Understanding the contribution of Resistance-Nodulation-Division family efflux pumps to the lifestyle of Pseudomonas aeruginosa - Scales, Danielle (2023)
Resistance-Nodulation-Division (RND) family efflux pumps are important antibiotic resistance determinants that extrude a range of structurally diverse antibiotics from the cell before they reach their target. Of the 12 RND efflux pumps in Pseudomonas aeruginosa, the best characterised are MexAB-OprM, MexCD-OprJ, MexEF-OprN and MexXY. The physiological requirement for so many efflux pumps is unclear given their varied and overlapping substrate profiles. To understand the reasons underlying so much redundancy, the impact of the loss of 10 of the individual efflux pumps and 9 combinatorial mutants lacking different combinations of efflux pumps was studied. In addition to changes in drug susceptibility, this study demonstrates that efflux also plays an important role in motility, quorum sensing, biofilm formation and virulence. Transcriptomic analysis revealed differences between a mutant lacking MexAB- OprM, MexCD-OprJ, MexEF-OprN and MexXY and the parental PAO1-L strain. Results validation using a combination of transcriptional promoter fusions and phenotypic assays revealed genes involved in quorum sensing, pyocyanin biosynthesis and efflux were upregulated at exponential growth phase. During stationary phase, genes related to anthranilate and glycerol metabolism were upregulated, while 13 tRNAs were downregulated. Interestingly, though the genes encoding several secreted exoenzymes were upregulated, the mutant produced significantly less alkaline protease, elastase B and protease IV than the parent strain. The results of this work provide new insights into the physiological roles of RND efflux pumps and demonstrate their role as much more than antibiotic resistance determinants.